Marketing Strategy Analysis of Perfect Diary - Liu, Zuxi (Transactions on Social Science, Education and Humanities Research, 2024)
From 2010 to the present, China's cosmetic market size has gradually grown and stabilized through sustained efforts, and people pay more and more attention to the promotion of Chinese culture. As the disposable income of Chinese people grows continuously, and at the same time, people are increasingly concerned about the external image, the use of national brands of color cosmetics has also been promoted. This paper focuses on the marketing strategy of Perfect Diary, using 4P analysis, STP analysis and SWOT analysis, to comprehensively analyze its market positioning, product innovation, channel expansion and social media operation. The study found that Perfect Diary has achieved rapid growth in brand awareness and market share by accurately targeting consumer groups, launching product series in line with trends, and combining online and offline multi-channel promotion. It also makes full use of social media platforms to effectively enhance brand influence. In addition, combined with the advantages and disadvantages of Perfect Diary's marketing strategy, this paper also gives suggestions for improvement. This study not only contributes to an in-depth understanding of Perfect Diary's success but also provides a useful marketing strategy reference for other cosmetic brands.